2012
DOI: 10.1002/gps.3889
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in satisfaction with and perceived benefit from mental health services: results from the collaborative psychiatric epidemiology surveys

Abstract: Our findings show clear evidence of age differences in satisfaction with and perceived benefit from MHS. The findings provide important implications for future interventions targeted to improve MHS satisfaction. Age-specific strategies should be developed to prevent delay in mental health treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
7
14
2
1
Order By: Relevance
“…Despite all participants being identified as having co-occurring mental health and substance use disorders, psychological issues appear to impact older adult participants' length of stay more than young adults' stay, whose main predictors appear to be more related to substance use issues. These results support others' findings that older age has been found to be associated with higher levels of mental health service satisfaction as well as perceived benefit of mental health services (Ford, Bryant, & Giyeon, 2012). Psychological concerns may be of greater perceived importance to older adult participants and this needs to be considered in treatment planning and intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Despite all participants being identified as having co-occurring mental health and substance use disorders, psychological issues appear to impact older adult participants' length of stay more than young adults' stay, whose main predictors appear to be more related to substance use issues. These results support others' findings that older age has been found to be associated with higher levels of mental health service satisfaction as well as perceived benefit of mental health services (Ford, Bryant, & Giyeon, 2012). Psychological concerns may be of greater perceived importance to older adult participants and this needs to be considered in treatment planning and intervention.…”
Section: Discussionsupporting
confidence: 91%
“…2 In reality NHS Mental Health Trusts (the legal entities) may comprise several different hospitals and may provide community services in many different localities, but for convenience we refer to these all as hospitals. + Bjorngaard et al (2007Bjorngaard et al ( , 2012, Ford et al (2013), Raleigh et al (2007), Robillos et al (2014) and Rosenheck et al (1997) − Eytan et al (2004 Disability [none] + Desai et al (2005) Disability/medical comorbidities − Holcomb et al (1998) and Kilbourne et al (2006 + (Holcomb et al 1998) − Edlund et al (2003 and Kilbourne et al (2006) Eligibility requires patients to have received specialist care for a mental health condition and to be seen in the community during the sampling period. Excluded patients, according to the 2010 eligibility criteria, were those seen only once for an assessment, patients receiving drug and alcohol, learning disability, or specialist forensic services, current inpatients, and patients who only see their GP for their mental health condition.…”
Section: Datamentioning
confidence: 99%
“…We also included a number of hospital-level characteristics. Among patient characteristics reported in Table 1, we included the hospitals' ethnicity composition of survey respondents, allowing us to account for potential lower satisfaction experienced by minority ethnic groups (Boydell et al 2012;Ford et al 2013). Ethnicity data was only available as a hospital-level aggregate weighted by age and gender.…”
Section: Dependent Variable and Covariatesmentioning
confidence: 99%
“…Previous findings from developed countries have yielded ambiguous results regarding the relationship between age and the quality of mental health services. For instance, whilst some studies concluded that adult age is inversely associated with increased satisfaction and access to services [55], others had contrary findings [56,57]. The differences in evidence from previous studies in developed countries could be attributed to the differences in the health care systems and individual demographics of the population.…”
Section: Plos Onementioning
confidence: 94%